Isolation and Sequencing of Actin1, Actin2 and Tubulin1 Genes Involved in Cytoskeleton Formation in Phytophthora cinnamomi - Martins, Ivone (2014)
Oomycetes from the genus Phytophthora are fungus-like plant pathogens that are devastating for agriculture and natural ecosystems. On the Nordeste Transmontano region (northeast Portugal), the Castanea sativa chestnut culture is extremely important. The biggest productivity and yield break occurs due to the ink disease, caused by Phytophthora cinnamomi which is one of the most widely distributed Phytophthora species, with nearly 1000 host species. The knowledge about molecular mechanisms responsible for pathogenicity is an important tool in order to combat associate diseases of this pathogen. Complete open reading frames (ORFs) of act1, act2 and tub1 genes who participate in cytoskeleton formation in P. cinnamomi were achieved by high-efficiency thermal asymmetric interlaced (HE-TAIL) polymerase chain reaction (PCR). act1 gene comprises a 1128 bp ORF, encoding a deduced protein of 375 amino acids (aa) and 41,972 kDa. act2 ORF comprises 1083 bp and encodes a deduced protein of 360 aa and 40,237 kDa. tub1 has a total length of 2263 bp and encodes a 453 aa protein with a molecular weight of 49.911 kDa. Bioinformatics analyses shows that actin1 is ortholog to the act1 genes of Phytophthora infestans, Phytophthora megasperma and Phytophthora melonis; actin2 is ortholog to the act2 genes of P. infestans, Phytophthora brassicae, P. melonis and Pythium splendens and tubulin1 shows the highest orthology to P. infestans and P. capsici α-tubulin genes. Analysed 3D structure of the three putative proteins revealed a spatial conformation highly similar to those described for orthologous proteins obtained by X-ray diffraction.